PERENCANAAN SISTEM PENYALURAN AIR LIMBAH DOMESTIK DI KELURAHAN MANARAP LAMA DAN DESA MANARAP TENGAH KECAMATAN KERTAK HANYAR - Nurul Qurrata A'yun; Riza Miftahul Khair; Muhammad Syahirul Alim; Chairul Abdi (Jernih: Jurnal Tugas Akhir Mahasiswa, 2025)
Manarap Lama and Manarap Tengah villages are located in Kertak Hanyar subdistrict with the hghest population density. High population density can affect the amount and quality of domestic wastewater produced. Access to sanitation in this area for ownership of Permanent Healthy Latrine is 92.37%, Semi-Permanent Healthy Latrine is 6.54%, and open defecation behavior is 1.09%. Domestic wastewater comes from various household activities such as bathing, washing, and latrines. Greywater is directly discharged into the river and blackwater is channeled into the septic tank without regular draining which can blend with river water. Thus causing the water quality in this area to exceed the quality standards set by PERMEN LHK No. 68 of 2016. Domestic wastewater treatment systems that have not been implemented can also have a negative impact on the sanitation conditions in this area. The purpose of this study is to analyze the existing condition of the area and then make a planning for the domestic wastewater distribution system. The research method is based on primary and secondary data collection and data analysis. In planning the domestic wastewater distribution system, three alternative pipelines are planned. Based on the results of the selection, alternative B is obtained as the chosen alternative route which has a channel length of 10,751 m, a flow time of 5.71 hours, requires 97 manholes, and a pipe cost investment of Rp1.848.051.349 (One Billion Eight Hundred Forty Eight Million Fifty One Thousand Three Hundred Forty Nine Rupiah).